Developing the Requirements of a PLM/ALM Integration: An Industrial Case Study - Deuter, Andreas; Otte, Andreas; Ebert, Marcel; Possel-Dölken, Frank (4th International Conference on System-Integrated Intelligence - Intelligent, Flexible and Connected Systems in Products and Production)
The digitization of the industry requires smart products and services. Smart products are mechatronic products with an increasing amount of software. To get high quality smart products to the market quickly, manufacturers need to reshape their product lifecycle processes. They need to apply system engineering-based methods to enable smooth cross-domain developments with a special focus on the software domain. One significant challenge faced by manufacturers is the harmonization of product lifecycle management (PLM), which addresses the hardware lifecycle, with application lifecycle management (ALM), which addresses the software lifecycle. To support manufacturers in this challenging activity, this paper demonstrates a proven process for developing use cases and requirements associated with a PLM/ALM integration. This process has been elicited during an industrial case study in a manufacturing company. This paper explains this process in detail. A generally applicable approach for developing the requirements of a PLM/ALM integration is extracted by removing the company-specific factors.
Keywords: Product lifecycle management; Application Lifecycle Management; Smart products; Systems engineering